2019
DOI: 10.21203/rs.2.9750/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of GeneXpert and Line Probe Assay for Detection of Mycobacterium tuberculosis and Rifampicin-Mono resistance at the National Tuberculosis Reference Laboratory, Kenya

Abstract: Introduction The dual challenge of low diagnostic sensitivity of microscopy test and technical challenge of performing a TB culture test poses a problem for case detection and initiation of Tuberculosis (TB) second-line treatment. There is thus need for a rapid, reliable and easily accessible assay. This comparative analysis was performed to assess diagnostic performance characteristics of GeneXpert MTB/RIF and Line Probe Assay (LPA) Methods 329 sputum samples of patients across the 47 counties in Kenya sus… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…Such difference between the two ndings might be due to the difference in number of drug resistant isolates. Further, the agreement between Culture MGIT and LPA in detecting katG, inhA and both (katG and inhA) resistance was almost perfect and agrees with a study from Kenya [22].…”
Section: Socio-demographic Characteristics Genotypic and Phenotypic supporting
confidence: 89%
See 1 more Smart Citation
“…Such difference between the two ndings might be due to the difference in number of drug resistant isolates. Further, the agreement between Culture MGIT and LPA in detecting katG, inhA and both (katG and inhA) resistance was almost perfect and agrees with a study from Kenya [22].…”
Section: Socio-demographic Characteristics Genotypic and Phenotypic supporting
confidence: 89%
“…In the case of freezed live Mycobacterium, its survival could be interrupted through time until it was sub-cultured using the MGIT instrument. The higher sensitivity result 94.2% of LPA and its lower speci city value 30.2% is comparable with similar settings done in Kenya where its sensitivity and speci city was 99.2 and 26.9%, respectively [22]. This showed that LPA has a good performance in detecting the true positivity of Mycobacterium and in a fair agreement (Kappa = 0.276; P < 0.001) with the BACTEC MGIT 960 performance.…”
Section: Socio-demographic Characteristics Genotypic and Phenotypic supporting
confidence: 77%
“…The variations observed in this study may have resulted from differences in diagnostic methods. Line probe assays reportedly have a higher sensitivity and specificity in detection of drug resistant Mycobacterium tuberculosis in comparison to GeneXpert and Sputum Acid-Fast Bacilli which are still the most frequently used diagnostic methods in many centers across southern Nigeria [8,17,30]. Therefore, TB and DRTB cases which would have been missed with other diagnostic methods may have been detected in this study.…”
Section: Discussionmentioning
confidence: 79%
“…One of these methods, the molecular line probe assay [LPA], GenoType®MTBDRplus, developed by HAIN Lifescience, Nehren, Germany for the molecular genotypic identification of MTBC and its resistance to rifampicin [RIF] and and/or isoniazid [INH] directly from clinical specimens as well as culture was approved in 2008 [15]. The use of LPA has improved the detection and treatment of drug resistant TB globally [16,17] via early and accurate diagnosis, with significantly lesser turnaround time [48 hours] as compared to conventional DST method [42 days]; thus enabling appropriate medication for treatment, especially in the presence of drug resistance, with a resultant break in the transmission cycle.…”
Section: Introductionmentioning
confidence: 99%